Correction of gradient‐induced phase errors in radial MRI. Issue 1 (25th February 2013) - Moussavi, Amir; Untenberger, Markus; Uecker, Martin; Frahm, Jens
<x xml:space="preserve">Abstract</x> Purpose To correct gradient‐induced phase errors in radial MRI. Methods Gradient‐induced eddy currents affect the MRI data acquisition by gradient delays and phase errors that may lead to severe image artifacts for non‐Cartesian imaging scenarios such as radial trajectories. While gradient delays are dealt with by respective shifts of the acquisition window during radial image acquisition, this work introduces a simple method for quantifying and correcting phase errors from the actual data prior to image reconstruction. For a given gradient system, the approach yields a specific phase error per gradient that can be used for correcting the raw data. Results Phantom studies at 9.4 T demonstrated marked improvements in radial image quality. It could be shown that the phase correction is not compromised by data undersampling. Moreover, the selective correction of gradient‐induced phase errors retained the phase information caused by different concentrations of a paramagnetic contrast agent. Conclusion The proposed method does not require additional reference measurements and separately corrects for phase errors induced by eddy currents, while retaining the residual phase of the object which may carry physiologic information. Magn Reson Med 71:308–312, 2014. © 2013 Wiley Periodicals, Inc.